Information integration in the functional areas "Supply Logistics" and "Production Logistics" in the management of engineering company - Simonova, Larisa; Shutova, Polina (Видавництво Львівської політехніки, 2013)
The article is devoted to the development of expert system for the management of material, financial and information flows in the functional areas “Supply Logistics” and “Production Logistics” within the product lifecycle management for engineering companies. A model of the product life cycle that characterizes the stage of procurement, production preparation and production of the product. Clarified the definition of “Integrated Logistics Support.” Research in the field of logistics, presented in the article focused on the development of methods for building an integrated information space and operational management systems, enabling enterprises to coordinate the processes of participating life cycle in real time.
Keywords: information integration; logistics; CALStechnologies; life cycle; integrated logistics support; procurement; production logistics